The Efficacy and Safety of Adding Olanzapine to Triple Drugs Regimen to Prevent Chemotherapy-induced Nausea and Vomiting: A systematic Review and Meta-analysis of RCTs - Sharanabasayyaswamy B. Hiremath; Srinivas L. Devendrappa (Pharmacology and Clinical Pharmacy Research, 2022)
Chemotherapy-induced nausea and vomiting (CINV) is a complication of highly emetogenic chemotherapy (HEC) agents. The present meta-analysis was conducted to quantify and analyze the efficacy and safety of adding olanzapine to a Neurokinin Receptor Antagonist (NKRA) based triple-drug regimen in preventing HEC-induced CINV. Electronic database searches in PUBMED and Cochrane library was conducted using MeSH search terms “olanzapine” and “chemotherapy-induced nausea and vomiting.” Randomized or cross-over trials comparing the efficacy of “olanzapine + NKRA based triple-drug regimen” vs. “placebo + NKRA based triple-drug regimen” in patients of age > 18 years with any malignancy receiving HEC were considered under inclusion criteria. Complete Response (CR) for the delayed (25–120 h) phase of CINV in patients receiving HEC agents was the primary outcome measure analyzed. Outcome measures were estimated by calculating the Risk Difference (RD) values and their 95% Confidence Intervals (CI). The Mantel-Haenszel method and both fixed and random effect models were used in the analysis by Revman 5.4.1 soft- ware. An additional 14% (RD: 0.14, 95% CI: 0.09 to 0.19) of patients treated with olanzapine + triple-drug regimen had a statistically significant higher CR in the delayed phase when compared to placebo + NKRA-based triple-drug regimen. Adding olanzapine at 10mg to the triple-drug regimen significantly improves delayed phase CR rates by 16% and delayed phase ‘no significant nausea’ rates by 30%. Results need to be interpreted cautiously in the background of response variations and limited trials included in our analysis